A Historical Exploration of Military-Driven Infrastructure Development: Lessons Learnt and Way Forward - Thapa, Subash (KTFT Journal, 2024)
Military-driven infrastructure development has emerged as a critical aspect of national security and global power dynamics. This paper delves into the historical nexus between military strategy and infrastructure development. It aims to provide key insights and chart a pathway for future discourse. The study employs a qualitative research approach to comprehensively analyse relevant literature comprising case studies, theoretical frameworks, and empirical studies to elucidate the evolution of military involvement in infrastructure projects. It examines the ancient civilizations spanning through medieval advancements, colonial expansion, and post-war reconstruction efforts to trace the pivotal historical moments where militaries played a decisive role in shaping infrastructure landscapes. Likewise, the study advocates for a nuanced approach that prioritizes sustainable development goals. The paper identifies key themes, highlighting the potential of military-led infrastructure initiatives and the necessity for clear delineation of military involvement. Thus, the study substantiates the symbiotic relationship between security imperatives, infrastructure development, and economic prosperity, and offers strategic recommendations for future military-driven infrastructure development from a historical perspective.